Determinants of community health center staff performance - Usman, Noernahar Septisari; Rosyidah, Rosyidah; Solikhah, Solikhah (Science Midwifery, 2025)
Employee performance is a key indicator reflecting the quality of services in community health centers. At Marisa Health Center, Pohuwato District, various service-related issues such as delays, unfriendly staff behavior, and late program report submissions indicated suboptimal employee performance. This study aimed to determine factors associated with staff performance at Marisa Health Center. A quantitative cross-sectional design was used, involving 108 staff selected through total sampling. Data were collected using a validated and reliable questionnaire and analyzed through univariate, bivariate (Chi-square test), and multivariate (logistic regression with the Backward Likelihood Ratio method) analyses, with ethical approval number KEPK/UMP/162/IV/2025. The results showed no significant association between performance and education (p = 0.983), work motivation (p = 0.087), or physical work environment (p = 0.432). However, significant associations were found for work discipline (p = 0.015; PR = 1.642), organizational culture (p = 0.036; PR = 1.519), and job satisfaction (p = 0.008; PR = 1.700). Job satisfaction was the dominant factor influencing performance (Exp(B) = 2.818; p = 0.014), suggesting that dissatisfied employees were nearly three times more likely to perform poorly. These findings highlight the importance of improving satisfaction, discipline, and culture to enhance staff performance.